Green swimming: getting into the energy saving rhythm - Sanders, R. (Applied Swimming Programme Schedule - 27th International Conference on Biomechanics in Sports, 2009)
Why is butterfly almost as fast as freestyle? By developing good rhythm and timing of body actions skilled butterfly swimmers are able to swim more economically than less skilled swimmers - almost as economically as freestyle! Implications for coaching and identification of swimmers suited to competitive butterfly swimming are discussed.